The complete chloroplast genome and phylogenetic analysis of Cyperus malaccensis Lam (Cyperaceae) - Lianghao Pan; Kun Chen; Xin Liao (Mitochondrial DNA. Part B. Resources, 2024)
AbstractCyperus malaccensis Lam is a perennial herbaceous plant that is distributed over a large area along the southern coast of China. Some plants of the Cyperaceae family are highly similar morphologically, which makes them difficult to classify and identify. In this study, the complete chloroplast genome of C. malaccensis was sequenced and assembled. The chloroplast genome is 186,098 bp long with a 33.18% content of GC. The structure of chloroplast genome includes a quadripartite structure that is composed of a pair of inverted repeats (IRs) of 37,434 bp, a small single copy (SSC) region of 10,296 bp, and a large single copy (LSC) region of 100,934 bp. The genome contains 141 genes, including 94 protein-coding genes, 39 tRNA genes, and 8 rRNA genes. A phylogenetic analysis showed that C. malaccensis is the most closely related to the congeneric species C. rotundus. These results enrich the genetic resources of the Cyperaceae and provide a molecular basis for further study on the phylogeny of this family.